TINGGI BADAN IBU TERHADAP KEJADIAN STUNTING PADA BALITA: LITERATURE REVIEW - Winda, Stella Agrifa (ProNers, 2023)
Backgrounds : Stunting is a short or very short state of the body that occurs due to the condition of growth and development. One of the causes of stunting is the mother's height. The mother's height is associated with the physical growth of the child. Short mother is one of the factors related to stunting. Objectives : identify the relationship of maternal height to stunting events in toddlers. Methods : This type of research is a literature review. Literature review is conducted by identifying from accredited resource persons and resources relevant to the theme of the discussion. The research method was conducted using the SPIDER framework. The selection of resource persons and resources is done using inclusion and exclusion criteria. The selected source is then reviewed. Results : Mother's height has an influence on stunting events in toddlers. Genetically short in the mother, will affect the height of the toddler. The characteristics of mothers who have short height carry genetic factors that cause stunted, because the genes carrying short chromosomes will most likely lower those short traits against their offspring. Height is a form of genetic expression, and is a factor passed down to children and related to stunting. Conclusion :   Mother's height affects the incidence of stunting in toddlers. Genetically, parents who have inherited genes in chromosomes with short height will pass down short traits to their children, because a person's genetics is inherited from parents through genes.